Evaluation of media literacy course according to school principals' opinions [Medya okuryazarliǧi dersi̇ni̇n okul müdürleri̇ ni̇n görüşleri̇ne göre deǧerlendi̇ ri̇lmesi̇] - (:unkn) unknown (My University, 2009)
Media literacy is defined as accessing, analyzing, evaluating and transmitting message skills in different written and unwritten formats: e.g. television, video, cinema, commercials, internet, etc. The purpose of this study is to evaluate media literacy education according to school principals' opinions through interview data collection. The study group for this research includes five school principals in five pilot cities in which interviews were the method for collecting data. Content analysis techniques were used for analysis. All five school principals agree with the necessity of media literacy education. They also say that media is a powerful tool both locally and globally, and students should be more conscious of its formidable power. However, they have different opinions regarding how it should be presented in school systems. Finally, principals reveal that if media literacy courses are to be conducted around the country, schools should be designed with better equipment and schoolparent cooperation increased as much as possible.
Keywords: Media literacy; Primary school; School principal